2010
DOI: 10.1177/112067211002000618
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Mydriasis in Cataract Surgery: Topical versus Mydriasert versus Intracameral Mydriasis in Cataract Surgery

Abstract: The most effective mydriasis was obtained within the Mydriasert group, followed by the topical mydriasis group. From the cardiovascular point of view, intracameral mydriasis was the safest and topical mydriasis the least safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 7 publications
4
40
0
2
Order By: Relevance
“…In our first two studies, we could se no signs of negative cardiovascular effects from intracameral myriatics (Lundberg and Behndig 2003;Behndig and Eriksson 2004), which is well in accordance with the facts that the doses of the adrenergic and anticholinergic substances are lower when the substance is administered intracamerally, and that there is likely to be a smaller proportion of the drug that enters the lacrimal drainage system with intracameral administration. Morgado et al confirmed in a study from 2010 involving 90 patients that topical mydriatics is more efficient from an initial mydriatic point of view, but intracameral mydriatics are safer from a cardiovascular point of view (Morgado, Barros et al 2010). Taken together, the reports on cardiovascular safety combined with the widespread clinical routine use of intracameral mydriatics are reassuring -the risk of systemic side effects is not likely to be higher with the intracameral route of administration.…”
Section: Cardiovascular Safetysupporting
confidence: 56%
See 1 more Smart Citation
“…In our first two studies, we could se no signs of negative cardiovascular effects from intracameral myriatics (Lundberg and Behndig 2003;Behndig and Eriksson 2004), which is well in accordance with the facts that the doses of the adrenergic and anticholinergic substances are lower when the substance is administered intracamerally, and that there is likely to be a smaller proportion of the drug that enters the lacrimal drainage system with intracameral administration. Morgado et al confirmed in a study from 2010 involving 90 patients that topical mydriatics is more efficient from an initial mydriatic point of view, but intracameral mydriatics are safer from a cardiovascular point of view (Morgado, Barros et al 2010). Taken together, the reports on cardiovascular safety combined with the widespread clinical routine use of intracameral mydriatics are reassuring -the risk of systemic side effects is not likely to be higher with the intracameral route of administration.…”
Section: Cardiovascular Safetysupporting
confidence: 56%
“…As we will see below, a local anesthetic will also have an additive, passive mydriatic effect when injected intracamerally (Cionni, Barros et al 2003). We early found that when using a regimen involving intracameral mydriatics, some of the disadvantages with topical mydriatics are avoided, since the method means no preoperative waiting time and also reduced doses of the mydriatic substances -and thereby likely lowers the risk for systemic side-effects (Lundberg and Behndig 2003) (Morgado, Barros et al 2010). In our own current setting, a preservative-free mixture of phenylephrine 1.5% and lidocaine 1% is used, but other solutions have been proposed and used clinically, mainly preservative-free epinephrine 0.025% with lidocaine 0.75%, or lidocaine 1% only.…”
mentioning
confidence: 99%
“…In the study by Kumar et al, a viscous solution of phenylephrine, 10%, was used, which likely led to greater systemic absorption (Table). As this study provided only Chawdhary et al, 10 1984 Kumar et al, 11 1985 Morgado et al, 12 2010 Mouly et al, 13 10 cases for each of the concentrations and times (overall weighting <5%) and as viscous phenylephrine is not commonly used in clinical practice, the study's results are not representative of BP and HR changes following phenylephrine application in clinical routine and are only retained as a worstcase scenario. No differences were found between studies that used phenylephrine alone and those that combined it with tropicamide, suggesting that concurrent application of tropicamide has no additional effect on BP.…”
Section: Effect On Bpmentioning
confidence: 78%
“…6 In a sample of persons with hypertension with a baseline BP variability of 10 mm Hg per half hour, BP variability at baseline was shown to be associated with target organ damage assessed by presence of arrhythmia, left ventricular mass index, cardiac volume on chest radiography, and retinal hypertensive changes 7 years later, independent of the existing hypertension. 18 In another study, systolic BP variability of 15 mm Hg or less was defined as normal, and an increase more than this was associated with an increased prevalence of ischemic heart disease, severe carotid artery stenosis, and carotid intima media Morgado et al, 12 2010 Mouly et al, 13 2006 Subtotal Phenylephrine, 10%, at 20-30 min after application Chawdhary et al, 10 1984 Yospaiboon et al, 16 2004 than 5 mm Hg is not likely to be of any clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Mydriasert® is an insoluble-matrix, sterile, cylindrical-shaped device containing phenylephrine and tropicamide, which are slowly released following placement into the conjunctival cul-de-sac. The insert, currently approved for use in adults, has been shown to provide an effective and stable mydriasis for surgical and diagnostic procedures [14-17], but has not been tested in patients younger than 18 years old. Interestingly, in adults requiring preoperative mydriasis, the device avoids repeated applications of drops, reducing the nursing time [15, 18].…”
Section: Introductionmentioning
confidence: 99%